The detection of oesophageal varices using a novel, disposable, probe‐based transnasal endoscope: a prospective diagnostic pilot study. (24th May 2016) - Sami, Sarmed S.; Ragunath, Krish; Wilkes, Emilie A.; James, Martin; Mansilla‐Vivar, Rodrigo; Ortiz‐Fernández‐Sordo, Jacobo; White, Jonathan; Khanna, Amardeep; Coletta, Marina; Samuel, Sunil; Aithal, Guruprasad P.; Guha, Indra Neil
Abstract: Background & Aims: Screening for oesophageal varices (OV) using conventional oesophagogastroduodenoscopy (C‐OGD) is invasive and requires costly monitoring, recovery, and decontamination facilities. We aimed to evaluate the technical feasibility, acceptability and accuracy of a novel, portable and disposable office‐based transnasal endoscope (EG Scan ™ ) compared to C‐OGD as the reference standard. Methods: This was a prospective cohort study. Consecutive adult patients with cirrhosis were invited to participate. All subjects underwent the two procedures on the same day performed by two endoscopists in a blinded design. Patients completed preference and validated tolerability (10‐point visual analogue scale (VAS)) questionnaires on day 0 and day 14 post procedures. Results: Forty‐five of 50 patients (90%) completed both interventions. Mean age was 59 years and OV prevalence was 49%. Patients reported higher preference (percentage) and better experience (mean VAS) with EG Scan compared to C‐OGD on day 0 (76.5% vs. 23.5%, P < 0.001; 7.8 vs. 6.8, P = 0.058, respectively) and day 14 (77.8% vs. 22.2%, P < 0.001; 7.0 vs. 5.5, P = 0.0013 respectively). Sensitivity and specificity of the EG Scan for the diagnosis of any size OV were 0.82 (95% confidence interval (CI) 0.60–0.95), and 0.78 (95% CI 0.56–0.93) respectively. Corresponding values for the diagnosis of clinically significant (medium/large) OV were 0.92 (95% CI 0.62–1.0), 0.97 (95% CI 0.84–1.0) respectively. No serious adverse events occurred. Conclusions: EG Scan accuracy was higher for the diagnosis of medium/large OV compared to any size OV. Patients' preference and overall experience of the EG Scan was favourable compared to C‐OGD 14 days after procedures.